Designing & developing e-College (e-CRS) as a web based application tool / Khadijah Abdul Rahman … [et al.] - Abdul Rahman, Khadijah; Mat Nawi, Nur Ainatul Mardiah; Nik Md Salleh, Nik Sarina; Azeman, Nur Fatin Syawani; Hamid, Roseliza (UiTM Press, 2022)
This paper discusses the designing and developing of the e-College System (e-CRS) as a web based application tool for registering student’s room and fee payment at UiTM Machang campus. This system can replace manual registration and long queues, saving time and money. The System development Life Cycle (SDLC) is used as a methodology in order to have a clearer stage for each phase involved. The stages comprise of planning, analysis, design, implementation and maintenance. The College administration department can easily record the number of students by using this system, so it is easier for students to apply virtually. The administrative staff can also trace student records efficiently, making it easier for future reference. This online application tool is very important, especially in the times of the Covid-19 pandemic.